Use of hydrogen and oxygen isotopes to understand evaporation from enclosed waterbodies - Qiu, Xinyi; Peng, Weihua; Sun, Linhua; Chen, Kai; Zhao, Xiang (Journal of Environmental Engineering and Landscape Management, 2022)
Getting information on evaporation is important for water resource protection and managing regional enclosed waterbodies. Some lake water samples were collected in May and June from a representative enclosed waterbody – the Pearl Lake, Suzhou, China – and the hydrogen and oxygen isotopes determined. Most samples taken in June have higher δ18O and δD values than those in May, indicating that there are differences between the intensity of evaporation of May and June. This was further confirmed by the water samples’ d-excess values, which were below the meteoric line. However, the variations of d-excess value have been shown to be influenced by source moistures or evaporation processes, which were controlled by the local environment, e.g., whether the water was shaded or not. The residual water quantities calculated were 53 to 63% and 49 to 56% for May and June, respectively, relative to the initial water, indicating that about 5% of the water evaporated between 5 May and 5 June.